2014
DOI: 10.1590/1516-1439.249413
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and microstructural characterization of Nodular Cast Iron (NCI) with Niobium Additions

Abstract: Nodular cast irons (NCIs) involve the inoculation and nodulization of 0.03 to 0.06wt% Magnesium, as well as the addition of Molybdenum, Chromium, Nickel, Copper and Vanadium, although the presence of Niobium is not common. The literature reports that Niobium leads to better mechanical properties of the NCIs, and recent results indicate that 0.5wt% Niobium increases the strength and the Charpy notch toughness of NCIs, but decreases its hardness, in relation to a similar NCI without Niobium. The present report s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…It can be concluded that the standard speed makes the crack rate in materials proportionate with its fracture standard. In this research, jagged and dimple fractures that were found in the fracture microstructure and the high elongation define the ductile fracture at 1.5 mm/s speed [4]. Figure 3 shows the cleavage appearances that make it brittle.…”
Section: The Description Of Tensile Test Resultsmentioning
confidence: 64%
“…It can be concluded that the standard speed makes the crack rate in materials proportionate with its fracture standard. In this research, jagged and dimple fractures that were found in the fracture microstructure and the high elongation define the ductile fracture at 1.5 mm/s speed [4]. Figure 3 shows the cleavage appearances that make it brittle.…”
Section: The Description Of Tensile Test Resultsmentioning
confidence: 64%
“…For all HSDI samples with different Nb content, a change in the phase fraction in the metallic matrix was observed, as well as the presence of small irregular particles randomly distributed and corresponding to polygonal primary NbC carbides. These particles form before the casting due to the high affinity between Nb and C atoms, so they are called primary carbides [18,21,22,[24][25][26][27][28][29][30][31]. Unlike other carbide-forming elements (Mo, Cr, and V), precipitation of NbC carbides occurs randomly throughout the material rather than by positive segregation.…”
Section: Microstructural Analysismentioning
confidence: 99%
“…Additionally, Nb has low solubility, especially in ferrous alloys with relatively high carbon content, such as cast iron. The presence of these particles in DI has been reported to improve corrosion resistance and provide good wear resistance with little change in austenite stability and graphite refinement [21][22][23][24][25][26]. However, the effects of a combination of high Si and Nb content on DI have not been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…However, this behaviour appears to have been modified by the type of microstructure developed in the samples on addition of CNSA. (Souza et al, 2014). It is envisaged that the corresponding modest level of hardness conferred on the samples will be beneficial in curtailing the conventional cast irons wear rate in service (Hatate et al, 2001).…”
Section: F Hardnessmentioning
confidence: 99%